2020
DOI: 10.22541/au.159057903.36437350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of resource limitation on the temperature dependence of mosquito population fitness

Abstract: Laboratory-derived temperature dependencies of life history traits are increasingly being used to make mechanistic predictions for how climatic warming will affect vector-borne disease dynamics, partially by affecting abundance dynamics of the vector population. These temperature-trait relationships are typically estimated from juvenile populations reared on optimal resource supply, even though natural populations of vectors are expected to experience variation in resource supply, including intermittent resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The negative effect of low-resource concentration on these traits delayed the onset of reproduction and population-level reproductive output, respectively. This finding--that juvenile traits contribute more to rm than adult traits--is consistent with general studies of fitness in organisms with complex lifecycles (Caswell 1978;Kammenga et al 1996;Huey & Berrigan 2001;Cator et al 2020), including mosquitoes (Juliano 1998;Huxley et al 2020).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The negative effect of low-resource concentration on these traits delayed the onset of reproduction and population-level reproductive output, respectively. This finding--that juvenile traits contribute more to rm than adult traits--is consistent with general studies of fitness in organisms with complex lifecycles (Caswell 1978;Kammenga et al 1996;Huey & Berrigan 2001;Cator et al 2020), including mosquitoes (Juliano 1998;Huxley et al 2020).…”
Section: Discussionsupporting
confidence: 87%
“…While recent studies have shown that resource availability can affect the rm TPC in aquatic ectotherms (Orcutt & Porter 1984;Koussoroplis & Wacker 2016;Thomas et al 2017), very studies have examined how the rm TPC in terrestrial arthropods may be shaped by variation in resource availability (but see Huxley et al 2020). Therefore, the question of whether and how temperature and resource depletion interact to modulate disease transmission together through effects on underlying vector traits remains open.…”
Section: Introductionmentioning
confidence: 99%